Influence of HIV status on the management of acute asthma exacerbations. Issue 1 (23rd December 2019) - Adrish, Muhammad; Roa Gomez, Gabriella; Cancio Rodriguez, Enny; Mantri, Nikhitha
Abstract : Background: An increased incidence of asthma has been suggested in patients with HIV. We aimed to compare the outcomes of HIV-positive and HIV-negative patients following hospital admission for asthma exacerbation. Methods: A retrospective chart review of patients hospitalised between January 2015 and December 2017 owing to asthma exacerbation with a known HIV status was conducted. Results: During the study period, 1242 patients with asthma were admitted. Of these, 462 patients had a known HIV status (358 HIV-negative, 104 HIV-positive) and were included. No differences in baseline demographics, including age, sex, body mass index and underlying comorbid conditions, were identified between the groups except that HIV-negative patients had higher incidence of underlying congestive heart failure. HIV-positive group had a significantly higher serum creatinine levels (1.117 (1.390) vs 0.813 (0.509), p=0.001), higher serum eosinophil levels (492.91 (1789.09) vs 243.70 (338.66), p=0.013) but had lower serum neutrophils (5.74 (3.18) vs 7.194 (3.59), p=0.0002) and lower serum albumin levels (3.754 (0.480) vs 3.94 (0.443), p=0.003) than the HIV-negative group, respectively. Non-invasive positive pressure ventilation (NIPPV) use was more frequent (54.8% vs 25.4%, p≤0.001) and the length of in-hospital stay (LOS) was longer in HIV-positive vs HIV-negative patients (3.346 days vs 2.813 days, p=0.015); no differences in mechanical ventilation use or intensive care unit admission were noted between the groups. In a subgroup analysis comparing HIV-negative with HIV-positive patients stratified by CD4 count, NIPPV use was more frequent and the LOS was longer in HIV-positive patients with CD4 counts≥200 cellsx 10 ∧ 6/L. In a multivariable regression model, HIV-positive status was independently associated with NIPPV use (OR 2.52; 95% CI 1.43 to 4.46) and a 0.55 day (95% CI 0.02 to 1.08) longer LOS in hospital. Conclusions: HIV-positive patients admitted with asthma exacerbation are more likely to require NIPPV and have longer LOS.